Bamboo Arch Avenue, Greeting from Jamaica, B.W.I. - (:unkn) unknown (Cleary and Elliott, Jamaica, B.W.I., 2009)
Road lined with bamboo creating a natural arch. There is a car in the distance. Description on the back of the postcard "Greeting from Jamaica, B.W.I. Bamboo Arch Avenue. This beautiful bit of road is located in the parish of St. Elizabeth and is over one mile in length." Affixed to the postcard are one 6d (5 cents) and one 2d (1 cent) Jamaica stamps.
Colour: Re-coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Postcards; Jamaica; Bamboo--Jamaica; Arches--Jamaica; Roads--Jamaica; St. Elizabeth (Jamaica)